Neutron reflection investigation of polymer layers adsorbed at the solid-liquid interface - Field, J; Toprakcioglu, C; Ball, R; Stanley, H; Rennie, A; Penfold, J; Barford, W (1990)
Neutron reflectrometry techniques were employed to investigate the profile of polymers adsorbed at the solid-liquid interface. An optically flat, single crystal quartz surface was used as a substrate, in contact with a polymer solution. The geometry employed, allowed the neutron beam to travel through the quartz and be reflected from the quartz-liquid interface, the reflectivity of which was measured both before and after polymer adsorption. The systems studied were: a) polystyrene (PS) adsorbed on quartz from cyclohexane (a poor solvent at 21°C) and b) polystyrene/polyethyleneoxide (PS/PEO) block copolymer of various molecular weights adsorbed on quartz from toluene (a good solvent at 21°C). The results indicate a compact adsorbed layer of thickness ca. 5 nm in system (a). In system (b), however, the chains are terminally attached to the quartz surface (via the PEO block) as PS does not adsorb to the substrate from toluene, the latter being a very good solvent.